Antecedent of Purchase Decisions on Social Commerce Tiktok Shop - Yosep Fristamara; Trianasari Trianasari; Putu Indah Rahmawati (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to test the influence of viral marketing, content marketing, online customer reviews, celebrity endorsers, flash sales, and word of mouth (WOM) variables on purchasing decisions at the TikTok Shop in Buleleng Regency. The total sample obtained was 238 respondents. The data in this study was collected using a closed questionnaire. Data were analyzed using multiple linear regression tests using SPSS. The research results show that partially and simultaneously, Viral marketing, content marketing, Online customer reviews, Celebrity endorsers, Flash sales, and Word of mouth have a positive and significant influence on purchasing decisions.